Research on simulation experiment of the corn seed precision metering device based on Pro/E. (10th January 2022) - Yan, Hui; Chen, Hanlin; Yu, Ping; Long, Duo
In this paper, a new type of corn precision seed metering device - combination inner-cell corn seed precision metering device and two kinds of corn are concerned. Considerable research on metering device modelling method of the complex structure of mechanical parts and discrete element method by Pro/E software is conducted. Through the identification and reading of boundary information, the binding of motion and material property, and data storage, the 3D discrete element analytical model from 3D Pro/ENGINEER physical model is realised. Furthermore, simulation analysis on the working process of precision seed metering device is conducted on the working platform integrated by CAE software, so that, the results acquired by experiments of seed metering device can be analysed contrastively for optimisation design of corn precision seed metering device.